PENGARUH AKUNTABILITAS PENGELOLAAN KEUANGAN ALOKASI DANA DESA DAN KELEMBAGAAN DESA TERHADAP PELAYANAN MASYARAKAT DESA CIDADAP KECAMATAN CURUGBITUNG - Usep Siswadi; Nurhaini Nurhaini; Evi Jayanti (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2021)
This study aims to examine the variable Accountability of Village Funds Management (X1) and Village Institutions (X2) that can affect the Community Services (Y) of Cidadap Village in Curugbitung District. The method used is descriptive quantitative with a population of Cidadap Village in Curugbitung District totaling 40 people consisting of RT, RW and Community Leaders. The Village Government must produce evidence of the realization of the accountability that becomes the Village Financial Aspect report, this report is the result of a Village Financial Management circulation, or starts from the level of planning, and budgeting, implementing and administering to reporting and taking responsibility for village financial management. The budget allocated from the Regional or Municipal Government to the Village originating from the Budget section of the central and regional financial considerations received by the region or city in order to support all fields in the community in the use of Village Fund Allocation, Techniques using Test Validity, Test Reliability. And Test Prerequisite Research with Classical Assumption Test. The Hypothesis Test consists of Multiple Linear Regression Analysis Test, Determination Coefficient Test, Correlation Analysis Test, and Partial t Test and Simultaneous Test f.Based on the results of research in the First Hypothesis states that the results of the test tcount 5.887 ttable 2.024 H1 received by having a significant value of 0,000 0.05 H0 rejected means that the variable Accountability of Financial Management Village Fund Allocation has a significant effect on Community Services in the Village of Cidadap in Curugbitung District, the Second Hypothesis states that the test results of tcount 4.288 ttable 2.024 H2 Received by having a significant value of 0,000 0.05 H0 is rejected, it means that the Village Institution variable has a significant effect on the Community Service in Cidadap Village in Curugbitung District and the Third Hypothesis states that the results of the f test show that the fcount 33.27 ft. H3 is accepted by having a significance value of 0,000 0.05 H0 rejected meaning that the Village Fund Allocation (X1) and Village Institution (X2) variables have a significant effect on the Village Community Services (Y) in Curugbitung District